Choose your own adventure [games] : House of danger : a cooperative adventure game - Montgomery, R. A. (Choose your own adventure., 2018)
"Object of the game: You are an aspiring detective and psychic investigator. For weeks, you have experienced recurring nightmares that you sense might be important. Your mission is to get to the bottom of these visions. You will decide how to move through the story as a grouop. The story is divided into five chapters, each of which is to be played in a single session." -- Instruction booklet, page 3.